2022
DOI: 10.22141/2224-1507.3.11.2013.82322
|View full text |Cite
|
Sign up to set email alerts
|

Оценка Возможностей Использования Австрийской Модели FRAX В Прогнозировании Риска Остеопоротических Переломов У украинских Женщин

Abstract: Резюме. В настоящее время методика FRAX является информативной и независимой в оценке риска остеопоротических переломов. С целью создания нормативных данных для австрийской модели алгоритма FRAX нами обследовано 3405 женщин в возрасте 40-89 лет. Анализ результатов FRAX выявил, что показатели FRAX-all и FRAX-hip соответственно 11,5 и 2,5 балла при использовании австрийской модели у постменопаузальных женщин являются критерием для начала терапии остеопороза. Показатели FRAX-all и FRAX-hip соответственно 7,0 и 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…The Ukrainian Scientific Medical Centre on Osteoporosis Problems (Kiev) has used FRAX to estimate the osteoporotic fracture risk since 2009 [9]. Rather than using a surrogate model, the Austrian version of FRAX was adopted for clinical practice [10]. Since then, data have become available on hip fracture incidence in the Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…The Ukrainian Scientific Medical Centre on Osteoporosis Problems (Kiev) has used FRAX to estimate the osteoporotic fracture risk since 2009 [9]. Rather than using a surrogate model, the Austrian version of FRAX was adopted for clinical practice [10]. Since then, data have become available on hip fracture incidence in the Ukraine.…”
Section: Introductionmentioning
confidence: 99%
“…Our studies based on the application of FRAX models, developed for other countries, to the Ukrainian men and women showed that in order to evaluate the fracture risk any models are applicable; however, it is the country-specific threshold values for treatment initiation or additional examination that are relevant [8,9]. Furthermore, our findings reveal that the criteria used in the US (and some other) guidelines for the treatment initiation (20 or more for all osteoporotic fractures, and 3 or more for the hip fractures) may not be applied to assay the fracture risk of the Ukrainian population, because when the neighboring countries' models were applied (at that time, Ukraine had no model of its own), the received values were much higher [10]. In order to avoid this, we've developed and suggested our own intervention criteria, based on the Austrian FRAX model [8,11], and those were successfully applied up to the original Ukrainian FRAX model's creation.…”
Section: Introductionmentioning
confidence: 85%